Design and Synthesis of 1-O- and 6′-C-Modified Heparan Sulfate Trisaccharides as Human Endo-6-O-Sulfatase 1 Inhibitors - Kuei-Yao Tseng; Kuei-Yao Tseng; Zheng-Hao Tzeng; Ting-Jen Rachel Cheng; Pi-Hui Liang; Pi-Hui Liang; Shang-Cheng Hung; Shang-Cheng Hung; Shang-Cheng Hung (Frontiers in Chemistry, 2022)
The extracellular human endo-6-O-sulfatases (Sulf-1 and Sulf-2) are responsible for the endolytic cleavage of the 6-sulfate groups from the internal D-glucosamine residues in the highly sulfated subdomains of heparan sulfate proteoglycans. A trisaccharide sulfate, IdoA2OS-GlcNS6S-IdoA2OS, was identified as the minimal size of substrate for Sulf-1. In order to study the complex structure with Sulf-1 for developing potential drugs, two trisaccharide analogs, IdoA2OS-GlcNS6OSO2NH2-IdoA2OS-OMe and IdoA2OS-GlcNS6NS-IdoA2OS-OMe, were rationally designed and synthesized as the Sulf-1 inhibitors with IC50 values at 0.27 and 4.6 μM, respectively.